KONDISI EKONOMI, STIGMA, DAN TINGKAT RELIGIUSITAS SEBAGAI FAKTOR DALAM MENINGKATKAN UPAYA PENCEGAHAN COVID-19 - Awis Hamid Dani; Cucu Herawati; Herlinawati Herlinawati; Syaeful Bakhri; Lilis Banowati; Nuniek Tri Wahyuni; R. Nur Abdurakhman (JURNAL KEDOKTERAN DAN KESEHATAN, 2021)
Since the World Health Organization (WHO) declared the COVID-19 outbreak a global pandemic on March 11, 2020, in addition to its impact causing health, psychological and social problems it also affects economic activity around the world which cannot cause long-term and considerable economic implications, p. This affects the Government and society in efforts to prevent and control Covid-19, as several countries impose lockdowns, quarantine, stay at home, business closures, and travel bans. The purpose of this study was to see the relationship between stigma, reduced levels of religiosity, and economic conditions with efforts to prevent Covid-19 in society. This type of research uses descriptive-analytic with a cross-sectional design and asks for data using a survey using a questionnaire instrument via an online google form. The population in this study was 86 respondents in Cirebon, West Java, Indonesia. Statistical analysis used bivariate analysis with Chi-Square and multivariate logistic regression. The results showed that there was a relationship between economic conditions and efforts to prevent Covid-19 with a value of P-value 0.001 (<0.05). There is a relationship between stigma and efforts to prevent Covid-19 with a P-value of 0.001. There is a relationship between the level of religiosity and efforts to prevent Covid-19 with a value of 0.022. Meanwhile, there is no relationship between prevention and efforts to prevent Covid-19 with a value  P-value of 0.933. Economic conditions are the most influential variables on the prevention of Covid-19 with an Odds Ratio (OR) of 5.7 and have a regression coefficient value of 0.63, meaning that someone who has a good economic condition has a high probability of taking preventive measures at 63%.